Apakah Green Innovation dan Corporate Governance Memengaruhi Kinerja ESG? - Widya Yorsalina; Widiastuty, Erna (Akuntansi & Ekonomika, 2025)
This study aims to analyze the influence of green innovation and corporate governance on ESG performance in Indonesian public companies. The ESG performance variable is measured by the ESG score. Meanwhile, the green innovation variable is measured by green product innovation and green process innovation. The corporate governance variable is measured by the size of the board of commissioners, the proportion of independent commissioners, and gender diversity. Sampling using a purposive method obtained a sample of 43 companies with 215 company-year observations. The results show that green process innovation and the size of the board of commissioners have a significant positive effect on ESG performance. Conversely, green product innovation, the proportion of independent commissioners, and gender diversity are not significant. The results of this study indicate that companies prioritize stakeholder interests in their business activities related to the environment.